The effect of focused communication tasks on instructed acquisition of English past counterfactual conditionals - Broszkiewicz, Anna (Studies in Second Language Learning and Teaching, 2011)
One important controversy connected with the effectiveness of grammar teaching seems to have been resolved as there is ample empirical evidence testifying to the positive effect of form-focused instruction on second language acquisition (Nassaji & Fotos, 2004; Norris & Ortega, 2000; Spada, 1997, 2010). Nevertheless, there are still a number of problems open to debate and awaiting concrete solutions, such as how to establish connections between form and meaning and find the best way to teach grammar for implicit knowledge, which, in the opinion of most SLA researchers (Ellis, 2006a, p. 95) and according to numerous theoretical positions, is a key driver of linguistic competence. One of the options available to language educators is to employ focused communication tasks, which “are designed to elicit production of a specific target feature in the context of performing a communicative task” (Ellis, 2001, p. 21). The aim of the study reported in this article was to explore the effect of focused communication tasks on the instructed acquisition of English past counterfactual conditionals when compared with contextualized practice activities. The results of two types of intervention were measured employing a number of data collection instruments with a view to tapping both the explicit and implicit knowledge of the participants of the study. Both types of instructional treatment were equally effective in helping learners develop the explicit knowledge of past unreal conditionals, but when it comes to the implicit knowledge of the aforementioned structure, the group instructed by means of focused communication tasks outperformed the other experimental group and the control group, as evidenced by the results obtained from the individually elicited imitation test and the focused communication task performed in pairs.